IoT-driven Environmental Support System for Smart Cities - Andre Kurniawan Pamudji (Soegijapranata Catholic University, 2023)
Smart city is a concept of urban development that integrates information and communication technology (ICT) to enhance efficiency, quality of life, and environmental sustainability. The implementation of smart city has become increasingly popular in the last five years, with many countries developing smart city initiatives, such as the